(3GdCZGfjs - (3Ydj Hf GdMSjf Hf eMeO Hf CMeO Hf GdgjKe GdeQhGfj GdCehj GdbQTj, CHh GdaQL GdCUHgGfj, J (B356 (3g` s
(3ChdgG (B:s
(3CNHGQ GdSjO hfSHg s
(3BNQgG (B:s
(3abGd dg GHf CHj YJjb jG MHjHi GeSc Yf gPG GdeOjM aeG jSeYg CMO GdG Xffi BNQ GdLRA GdKGef ef cJGH GdCZGfi GdcHjQ s
(3HChdg dhMI eUhQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B278s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs